2004
DOI: 10.1080/1042819042000219458
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Function in Patients Treated for Leukemia in Childhood

Abstract: Ovarian and testicular function were assessed in 67 long-term survivors (37 females, 30 males) treated for leukemia between 1973 and 1992. At diagnosis they were 1-16 (median 5) years old and had evaluation of gonadal function 4-25 (median 13) years later at the age of 13-31 (median 19). All had been treated with various combinations of chemotherapy (ChT) (including cyclophosphamide (CYC) and cytarabine in 32 patients), 62 patients had received prophylactic cranial irradiation with 12-49 (median 18) Gy, 2 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…One study showed a relationship between ovarian dysfunction and increased serum lipid levels [58] and another one showed that survivors of testicular cancer with a hypogonadism had a higher waist-to-hip ratio (p = 0.045) and higher diastolic blood pressure (p = 0.014) than survivors without hypogonadism [59]. Because development of gonadal dysfunction after childhood cancer treatment has been widely described [60][61][62][63][64], we need to elucidate the possible relationship between gonadal dysfunction and abnormal changes in body composition, also in childhood cancer survivors.…”
Section: Gonadal Dysfunction After Earlier Childhood Cancer Treatmentmentioning
confidence: 97%
“…One study showed a relationship between ovarian dysfunction and increased serum lipid levels [58] and another one showed that survivors of testicular cancer with a hypogonadism had a higher waist-to-hip ratio (p = 0.045) and higher diastolic blood pressure (p = 0.014) than survivors without hypogonadism [59]. Because development of gonadal dysfunction after childhood cancer treatment has been widely described [60][61][62][63][64], we need to elucidate the possible relationship between gonadal dysfunction and abnormal changes in body composition, also in childhood cancer survivors.…”
Section: Gonadal Dysfunction After Earlier Childhood Cancer Treatmentmentioning
confidence: 97%
“…Slovene Ministry of Science has been financing the program for “Late effects of childhood cancer treatment” since 1993. Survivors included in the program have been evaluated and analyzed as to their late somatic sequelae including neurological deficits [17], endocrine function deficits [18], renal function damage [19], secondary tumors [20,21], cardiac damage [22], and psychosocial consequences [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Endocrine glands, gonads in particular, are very susceptible to damaging effects of anticancer therapy 5. The damaging effect of both ChT and radiotherapy (RT) on gonads is well known 6. In a study of 2283 long-term survivors of childhood cancer Byrne and colleagues found that RT below the diaphragm depressed fertility in both sexes for about 25%, ChT with alkylating agents with or without RT below the diaphragm depressed fertility by 60% in men, but in women alkylating agents therapy administered alone had no apparent effect on fertility 7…”
Section: Introductionmentioning
confidence: 99%